Migration During COVID-19 Pandemic in Industrial City: Case in Batam City, Indonesia - Chantira Saifimar; Agus Joko Pitoyo; Muhammad Arif Fahrudin Alfana (Populasi, 2023)
COVID-19 is a disease which has spread throughout the entire world and was announced as a pandemic as it infects individuals through air. As a result, policies regarding mobility and health protocols were implemented. Cities and regencies in Riau Islands act as the entrance gate to Indonesia from other countries due to its strategic locations thus migration became a very concerning thing, especially in Batam, a successful city in industry, commerce, and tourism. This study aims to identify the migration flow to and from Batam City to other regions in Riau Islands Province. This research used quantitative methods and data of people who switched domiciles from and to Batam in the scope of Riau Islands Province provided by the Population and Civil Registration Service of Batam City. After being analyzed descriptively, this study shows the number of migrants in and out of Batam fluctuated throughout 2019- 2021. The destinations and origins of migrants varied and show that distant regions were less demanded. This is due to the limited access and implementation of the mobility policies implemented during COVID-19. Reasons to migrate mostly are for work with a percentage around 16.5 to 22.7 percent and family with a percentage around 12 to 17.6 percent. However, around half of the migrants from 2019 to 2021 chose “Others” with no further specifications from the data provided.